Ambulance Personnel’s Experiences With Prehospital Births: A Qualitative Study in Aotearoa New Zealand - Withanarachchie, Vinuli; Todd, Verity; Dicker, Bridget; Maessen, Sarah E (SAGE Publications, 2025)
Births in the prehospital setting are infrequent yet associated with increased odds of maternal and neonatal morbidity and mortality. There is limited understanding of the experiences of emergency medical services staff in handling these potentially high-risk situations. We explored the perspectives of ambulance personnel in Aotearoa New Zealand when responding to out-of-hospital births. Hato Hone St John Ambulance is the largest emergency medical services provider in Aotearoa New Zealand. Between October and November 2023, all Hato Hone St John frontline staff were invited to complete an online survey, including open text questions about their experiences and challenges attending unplanned births. Data was coded and organised into themes using NVivo software and the inductive approach to thematic analysis. One hundred and forty-seven responses were received and included in the survey. Participants encountered a range of challenges in providing intrapartum care in the prehospital setting. Two key themes were identified: (1) navigating complexity and uncertainty in unplanned births, and (2) practical challenges and unsuitable environments; with several subthemes demonstrating that the ambulance personnel responded to obstetric emergencies in diverse circumstances, diligently working to deliver optimal care for both mothers and neonates. This study describes novel challenges faced by ambulance personnel attending unplanned births in Aotearoa New Zealand alongside obstacles previously reported by emergency medical services in other jurisdictions. These findings may be invaluable in guiding further research, curriculum and resource development to better prepare ambulance personnel for the challenging and uncertain situations that characterise prehospital birth events.
Keywords: 4203 Health Services and Systems; 32 Biomedical and Clinical Sciences; 4206 Public Health; 42 Health Sciences; Clinical Research; Emergency Care; Pediatric Research Initiative; Health Services; 8.1 Organisation and delivery of services; Reproductive health and childbirth; Generic health relevance; 3 Good Health and Well Being